Analysis of the Effect of Work Discipline and Compensation on Employee Performance Through Work Motivation at KPP Pratama Jakarta Gambir Tiga - Muhammad Ali Akbar (Madani Connection, 2024)
This study aims to examine the effect of work discipline and compensation on employee performance through work motivation. This research was conducted at KPP Pratama Jakarta Gambir Tiga with a population of 67 employees. The sampling technique in this study using nonprobability sampling technique. Namely a sampling technique that does not provide equal opportunities or opportunities for each element of the population member to be selected into a sample where the population size is the same as the sample size. This research uses quantitative methods by distributing questionnaires to employees of KPP Pratama Jakarta Gambir Tiga and taking a number of books, journals, and examples of previous research related to this research. The data analysis method used in this research is regression analysis, descriptive analysis, and path analysis. The results showed that work discipline and compensation affect work motivation.